Angiotensin-Converting Enzyme 2 (ACE2) in the Pathogenesis of ARDS in COVID-19 - Kuba, Keiji; Yamaguchi, Tomokazu; Penninger, Josef M. (Frontiers in Immunology, 2021)
Seventeen years after the epidemic of SARS coronavirus, a novel coronavirus SARS-CoV-2-emerged resulting in an unprecedented pandemic. Angiotensin-converting enzyme 2 (ACE2) is an essential receptor for cell entry of SARS-CoV-2 as well as the SARS coronavirus. Despite many similarities to SARS coronavirus, SARS-CoV-2 exhibits a higher affinity to ACE2 and shows higher infectivity and transmissibility, resulting in explosive increase of infected people and COVID-19 patients. Emergence of the variants harboring mutations in the receptor-binding domain of the Spike protein has drawn critical attention to the interaction between ACE2 and Spike and the efficacies of vaccines and neutralizing antibodies. ACE2 is a carboxypeptidase which degrades angiotensin II, B1-bradykinin, or apelin, and thereby is a critical regulator of cardiovascular physiology and pathology. In addition, the enzymatic activity of ACE2 is protective against acute respiratory distress syndrome (ARDS) caused by viral and non-viral pneumonias, aspiration, or sepsis. Upon infection, both SARS-CoV-2 and SARS coronaviruses downregulates ACE2 expression, likely associated with the pathogenesis of ARDS. Thus, ACE2 is not only the SARS-CoV-2 receptor but might also play an important role in multiple aspects of COVID-19 pathogenesis and possibly post-COVID-19 syndromes. Soluble forms of recombinant ACE2 are currently utilized as a pan-variant decoy to neutralize SARS-CoV-2 and a supplementation of ACE2 carboxypeptidase activity. Here, we review the role of ACE2 in the pathology of ARDS in COVID-19 and the potential application of recombinant ACE2 protein for treating COVID-19.